PENGARUH AUDIT FEE, ROTASI SEMU AUDIT DAN LAMANYA HUBUNGAN KLIEN DENGAN KANTORKUNTAN PUBLIK TERHADAP INDEPENDENSI AKUNTAN PUBLIK: Studi Kasus pada Kantor Akuntan Publik PwC Indonesia - Grace Bakri, - (2018)
The purpose of this study is to examine the effect of audit fee, pseudo rotation of audit and length of client relationship with audit of independence of public accountant. The population in this study is Public Accounting Firm (KAP) PricewaterhouseCoopers (PwC) Indonesia. Sampling is done by using purposive sampling method which yield 60 samples of auditor. Data analysis used in this research is multiple linear regression. The results of this study indicate that (1) Audit Fee has significant influence on the independence of Public Accountant, (2) Pseudo Rotation has significant influence to Public Accountant Independence, and (3) Length of Client Relationship with Public Accountant Firm has significant influence to Independence of Public Accountant.